Pengembangan Keswadayaan Kelompok PEW sebagai Strategi Pemberdayaan Ekonomi Berbasis Kewilayahan di Kota Yogyakarta - Yuli Kurniyati; Bening Hadilinatih (Universitas Proklamasi 45 Yogyakarta, 2015)
Areas Based Economic Empowerment Program (Program Ekonomi Berbasis Kewilayahan/PEW) is a program designed to focus on the learning process and empowercommunities through local economic institutions to shore up the economy of thecommunity itself. This study aims to: 1). Knowing the PEW Group self-reliance inorganizing services to members in order to regionally based economic empowerment.2). Identifying the factors management, member participation and partnership thathinder or support the PEW Group self-reliance and self-reliance opportunities for effortsto develop a support group for regionally based economic empowerment, 3). Formula tepolicy recommendations for the city authorities to develop and implement a model ofselfreliance development PEW group as a regionally based economic empowerment strategy in the city of Yogyakarta. This research is qualitative research, the research took place in the townYogyakarta. The collecting data techniques used were: study documentation, participant, observation, in-depth interviews, and focus group discussion (FGD). In the first studywere: 1). Evaluating Performance PEW Group 2). Identify factors inhibiting andsupporting self-sufficiency Group 3). Self-Supporting analyze PEW Group 4). Early formulation compile policy recommendations group. The research development model of self-reliance. Year II study is 1). Self-Supporting Group to develop a model based onthe results of Phase I study 2). Validation conduct joint FGD Stakeholder Model through3). Develop Model Self-Supporting Implementation Handbook. Results showed that the level of self-reliance menilitian PEW group is still low. This isreflected in the level of independence that is still low, both in terms of independence inthe administration, self-reliance and independence in the management of the assets. PEW group of selfsufficiency level is still low, due to several factors, namely: (1) Capacity Board PEW Group is still low (2) The lack of participation of members of the Group, and (3) lack of stakeholder support. Another factor that still require serious treatment that can increase self-reliance PEW Group is a factor Assistance Group Implementation and Monitoring and Evaluation during implementation is still lacking.